A structural analysis of M protein in coronavirus assembly and morphology - Neuman, Benjamin W.; Kiss, Gabriella; Kunding, Andreas H.; Bhella, David; Baksh, M. Fazil; Connelly, Stephen; Droese, Ben; Klaus, Joseph P.; Makino, Shinji; Sawicki, Stanley G.; Siddell, Stuart G.; Stamou, Dimitrios G.; et al. (Journal of structural biology, 2011)
The M protein of coronavirus plays a central role in virus assembly, turning cellular membranes into workshops where virus and host factors come together to make new virus particles. We investigated how M structure and organization is related to virus shape and size using cryo-electron microscopy, tomography and statistical analysis. We present evidence that suggests M can adopt two conformations and that membrane curvature is regulated by one M conformer. Elongated M protein is associated with rigidity, clusters of spikes and a relatively narrow range of membrane curvature. In contrast, compact M protein is associated with flexibility and low spike density. Analysis of several types of virus-like particles and virions revealed that S protein, N protein and genomic RNA each help to regulate virion size and variation, presumably through interactions with M. These findings provide insight into how M protein functions to promote virus assembly.